Evaluación del efecto de la dieta barf como coadyuvante en pacientes caninos con problemas de dermatitis atópica alimentaria - Aguilera Nicolalde, Heidy Joseth (2025)
The objective of the present investigation is to evaluate the effect of the BARF diet as a coadjuvant in canine patients with food atopic dermatitis problems. Establishing as methodology the use of 16 canine patients clinically diagnosed with atopic dermatitis, 4 patients were randomly divided into the following experimental groups; T1: BARF diet with sweet clover, T2: BARF diet with pork, T3: BARF diet with lamb and T4: BARF diet with turkey, the treatments were administered for 8 weeks, in addition, to measure the effect of the diets it was proposed; to evaluate the areas of pruritus, intensity of pruritus, IgE concentration, analysis of hematological biometry, before and after the administration of the treatments, considering that, 100% of the patients presented clinical manifestations that allowed to diagnose that they suffered from atopic dermatitis. As results it was determined that the patients under study presented an intensity of pruritus of 8 to 10 points, likewise the pre-treatment IgE concentration was found to exceed the maximum established reference value (50 - 150 mg/dL) with an overall mean of 171.47 mg/dL, in addition, the findings of the blood biometry showed that 100% of the patients presented values above the eosinophil reference value, likewise in the red line patients with polycythemia and hemoconcentration were observed. After the experimental period it was determined that the intensity of pruritus was reduced to 4 points, the post-treatment serum IgE concentration was significantly reduced with an overall mean of 105.32 mg/dL, additionally the values of the eosinophil count were reduced to be established between the referential range, in addition, the supply of the diets studied covered the nutritional requirements of the patients. It is concluded that BARF diets are a mitigating alternative for canine alimentary atopic dermatitis.